Analisis Pelaksanaan Praktikum Biokimia Topik Enzim pada Masa Pandemi Covid-19 - Gun Gun Gumilar; Asep Kadarohman; Nahadi Nahadi; F. M. Titin Supriyanti (Jurnal Penelitian Pendidikan IPA, 2023)
The COVID-19 pandemic is a new situation that brings challenges to all sectors, including education. One of the impacts is that there is an adjustment in the implementation of learning, including practicums, which are usually held offline, turning into online learning. In this study, an analysis of the implementation of biochemistry practicum was carried out for two semesters during the Covid-19 pandemic. This study uses a descriptive case study design. Research data obtained from document analysis and questionnaires. There are five classes used as samples of this study. Questionnaires were given to 116 students. The results showed that the implementation of the biochemistry practicum had been carried out well. This is marked by positive responses from students through questionnaires. Even so, there are significant differences in student achievement compared to conditions after the pandemic. This shows that practicum activities, especially those related to laboratory skills, cannot be facilitated with online learning